The Solander Trail : an innovative hiking trail development process based on the Experience Economy paradigm - Gelter, Hans (Luleå tekniska universitet, Medier ljudteknik och upplevelseproduktion och teater, 2013)
Godkänd; 2013; Bibliografisk uppgift: Abstract For the 22nd Nordic Symposium in Tourism and Hospitality Research “Innovation and value creation in experience-based tourism”, Bodö & Lofoten, September 24-27, 2013 20130508 (hage) Friluftsliv och naturturism ur ett upplevelseperspektiv